A Cell-Based Platform for the Investigation of Immunoproteasome Subunit β5i Expression and Biology of β5i-Containing Proteasomes - Alexander Burov (MDPI AG, 2021)
The degradation of most intracellular proteins is a dynamic and tightly regulated process performed by proteasomes. To date, different forms of proteasomes have been identified. Currently the role of non-constitutive proteasomes (immunoproteasomes (iPs) and intermediate proteasomes (intPs)) has attracted special attention. Here, using a CRISPR-Cas9 nickase technology, four cell lines: histiocytic lymphoma, colorectal adenocarcinoma, cervix adenocarcinoma, and hepatocarcinoma were modified to express proteasomes with mCherry-tagged β5i subunit, which is a catalytic subunit of iPs and intPs. Importantly, the expression of the chimeric gene in modified cells is under the control of endogenous regulatory mechanisms and is increased following IFN-γ and/or TNF-α stimulation. Fluorescent proteasomes retain catalytic activity and are distributed within the nucleus and cytoplasm. RNAseq reveals marginal differences in gene expression profiles between the modified and wild-type cell lines. Predominant metabolic pathways and patterns of expressed receptors were identified for each cell line. Using established cell lines, we demonstrated that anti-cancer drugs Ruxolitinib, Vincristine and Gefitinib stimulated the expression of β5i-containing proteasomes, which might affect disease prognosis. Taken together, obtained cell lines can be used as a platform for real-time studies of immunoproteasome gene expression, localization of iPs and intPs, interaction of non-constitutive proteasomes with other proteins, proteasome trafficking and many other aspects of proteasome biology in living cells. Moreover, the established platform might be especially useful for fast and large-scale experiments intended to evaluate the effects of different conditions including treatment with various drugs and compounds on the proteasome pool.